A fusion prognostics method for remaining useful life prediction of electronic products - Shunfeng Cheng; Pecht, M. (2009 IEEE International Conference on Automation Science and Engineering, 2009)
Prognostics and health management methods can provide advance warning of failure; reduce the life cycle cost of a product by decreasing inspection costs, downtime, and inventory; and assist in the design and logistical support of fielded and future electronic products. Traditional prognostic methods, such as data-driven methods and physics of failure methods have some limitations. This paper presents a fusion prognostics method, which fuses data-driven methods and physics of failure methods to predict the remaining useful life of electronic products. This method integrates the advantage and overcome the limitations of the data-driven methods and the physics of failure methods to provide better predictions.